Performance Estimation and Control Analysis of AC-DC/DC-DC Hybrid Multi-Port Intelligent Controllers Based Power Flow Optimizing Using STEM Strategy and RPFC Technique - C. Nagarajan; B. Tharani; S. Saravanan; R. Prakash (International Journal of Robotics and Control Systems, 2022)
The control system will measure the renewable energy generation power, and if the generated power is equal to the grid power, the generation sources are directly connected to the load system. When the power generation is not at sustaining level, the controller will optimize the source using the DC-DC converter and Battery based Energy management system. The operation of the battery system depends upon the power generation availability of renewable energy resources. During the high power RES, the battery is charging condition. When the RES is low power means the battery is in discharged condition. Also, the fuel cell-based energy compensation will take place when the battery power is low. The Energy router will monitor all the above generation plants based on the threshold values of each power plant, substantial Transformative Energy Management (STEM) Strategy and Resilient Power Flow Control (RPFC) controller takes necessary action like which power plant is connected to the grid power system. The simulation is performed on Mat lab / Simulink simulation platforms, and the results show the effectiveness and reliability of the control strategy for micro-grid interconnection and flexible energy flow correspondence.